Effects of foreign direct investment and trade openness on tax earnings: A study of selected Sub-Saharan African economies - Cordelia Onyinyechi Omodero; Joy Limaro Yado (Economies, 2024)
Every economy's prosperity is determined by the quantity of tax income it receives. Over the years, studies have demonstrated that inflows from foreign investments and openness to international trade are important contributors to a country's tax income. Based on this assumption, this study seeks to examine the impact of foreign direct investment (FDI) and open trade on tax income in a number of sub-Saharan African nations. The World Bank Development Indicators data on tax revenue, FDI, exports, imports, and exchange rates from 1990 to 2022 are used in the study. We also use the pooled mean group/panel autoregressive distributed lag approach to examine the data gathered for this inquiry. The results reveal that, in the long term, FDI has a significant negative impact on tax income; nevertheless, in the short run, Ghana's tax revenue collection suffers while other nations profit from FDI. The results reveal that Nigeria's exporting is detrimental to tax revenue collection, but South Africa's export of goods and services is beneficial. However, imports and currency rates benefit Nigeria, Ghana, and South Africa in the near term. Thus, the research suggests improving tax rules and administration to prevent the movement of resources by foreign investors out of the host countries in order to avoid the imposition of huge tax burdens on their firms. Countries with low exports, such as Nigeria, are urged to enhance local manufacturing to meet international export standards in order to alleviate the continual negative balance of payments, which is primarily fixed by the adequate export of products and services.
Keywords: H25; M16; 330; tax revenue; FDI; trade openness; export; import; exchange rate